Peran public relations dalam membangun citra positif industri bank syariah di Indonesia - Fachruddin, Mukhammad Hafidh (Maliki Interdisciplinary Journal, 2024)
The Islamic banking industry in Indonesia has experienced significant growth, but challenges in building and maintaining a positive image remain. A positive image is very important to increase customer trust and loyalty, as well as protect the reputation of Islamic banks in the midst of intense competition. This article discusses the strategic role of public relations (PR) as a communication bridge between Islamic banks and the community. This research uses descriptive analytical techniques to identify the various roles of public relations in building a positive image of the Islamic banking industry in Indonesia. The role found is that through various structured programs and activities, PR can create positive perceptions that are in line with sharia financial values ​​that are fair, transparent and ethical. Apart from that, PR also plays a role in managing crisis communications and sensitive issues that can damage the image of Islamic banks. Thus, effective PR management can strengthen the reputation of sharia banks and support the growth of the sharia financial industry in Indonesia.